SAT0534 Effect of sustained- release symptomatic drugs on progression of knee joint osteoarthrosis in patients with less than 5 years disease duration in a 5-year prospective study. (15th June 2017) - Kashevarova, N; Taskina, E; Alekseeva, L
Abstract : Objectives: To assess the effect of sustained release symptomatic drugs chondroitin sulfate (CS) + glucosamine hydrochloride (GH) on progression of knee OA in pts with <5 years disease duration during the 5year follow-up period (FUP). Methods: This 5-year study included 52 female-patients with primary knee OA (ACR criteria), disease duration did not exceed 5 yrs (mean age–59, 1±8, 9). On each pts the individual file including 200 parameters was filled. Diagnostic modalities used in each patient included plain radiography of knee joints (gonarthrosis stage was classified using Kellgren J.- Lawrence J. scale), DEXA subchondral portions of the hip and tibia, ultrasound (US) and MRI examination of knee joints. First OA stage was documented in 22 (42, 3%)pts, 2-nd - in 24 (46, 2%), 3d- in 6 (11, 5%). During 5 years of FUP 31 (60%) pts were administered the combined CS+GH regimen for more than 6 months a year. OA progression was documented based on radiographic criteria. Results: During the 5 year FUP radiographic progression (upgrade in radiographic stage) of knee OA was documented in 14 pts (Group 1 - with OA progression), while in 38 pts radiographic stage remained unchanged (Group 2 - without progression). Patients from both groups were comparable in terms of age and disease duration (p>0, 05). Although, pts from Group 1 with OA progression had more intense knee pain when walking: 60, 4±18, 3 vs 48, 7±17, 8mm, p=0, 04; and higher BMI values: 34, 5±4, 6 vs 28, 9±4, 9 kg/m 2, p=0, 001; US-findings based higher rate of synovitis:57, 1% vs 18, 4%, OR=5, 9, 95% CI 1, 6–22, 5, p=0, 009; bone marrow edema in medial tibia aspect 64, 3% vs 13, 2%, OR=11, 9, 95% CI 2, 8–50, 3, p=0, 0006 based on MRI findings. In pts with OA progression DEXA examination identified significantly higher absolute BMD values in the medial condyle of the tibia (0, 9 (0, 8–1, 2) vs 0, 8 (0, 7–0, 8) g/cm 2, p=0, 001) as compared to pts from Group 2. Re-examination in 5yrs showed that statistically significant differences between the two groups still remained. Analysis of 5year therapy revealed, that the majority of pts without OA progression (68, 4%) were taking combined CS+GH regimens for more than 6 months a year during 5-year FUP, while only 35, 7% of pts who progressed (OR=4, 3, 95% CI 1, 1–16, 3, p=0, 03) managed to adhere to this regimen. Discriminant analysis showed that 5-year intake of combined CS+GH therapy for more than 6 months a year should be considered as a predictor of decreased risk of disease progression, while on the contrary, such symptoms as synovitis, bone marrow edema, and high BMD values in the medial condyle of the tibia should be viewed as predictors and risk factors for knee OA progression in pts with <5 years disease duration. Based on identified factors and their coefficients the authors designed a model (with area under the ROC curve equal to 0, 93), allowing to predict the future course of the disease in an individual patient with high accuracy, i.e. 85, 7% sensitivity and 84, 2% specificity. Conclusions: Use of combined CS+GH regimens for more than 6 months a year during 5 years is an important factor, decelerating the progression of knee OA in pts with <5 years disease duration by the factor of 4. While synovitis, bone marrow edema, and high BMD values in the medial condyle of the tibia are responsible for further OA progression on this group of pts. Disclosure of Interest: None declared